PENGUATAN LITERASI SAINS DENGAN AUGMENTED REALITY BERBASIS ETNOSAINS UNTUK MEWUJUDKAN GENERASI UNGGUL DI SDN 101749 KLUMPANG - Fahrur Rozi; Halim Simatupang; Fahmy Syahputra; Yusron Abda’u Ansya (Universitas Negeri Medan, 2026)
Abstract: This Community Service activity aims to improve the quality of science learning at SDN 101749 Klumpang thru the integration of Augmented Reality (AR) technology and ethnoscience values. The partner for this activity is SDN 101749 Klumpang, which serves as the elementary school partner for developing learning innovation. The implementation method includes five main stages: socialization, training, technology application, mentoring, and evaluation. The results of the activity show a significant improvement in students' science literacy, with the following pretest-posttest average scores: science concept understanding increased from 56 to 88 (+32), ethnoscience analysis from 56 to 84 (+28), and observation skills from 56 to 86 (+30), resulting in an overall average increase of 30%. Additionally, there was an improvement in teachers' competence in integrating AR and local wisdom into learning. With the support of ongoing training and mentoring, this program demonstrates that collaboration between technology and local culture can create science learning that is interactive, contextual, and relevant to the educational challenges of the 21st century. Keyword: Science Literacy, Augmented Reality, Ethnoscience, Elementary School Abstrak: Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk meningkatkan kualitas pembelajaran sains di SDN 101749 Klumpang melalui integrasi teknologi Augmented Reality (AR) dan nilai-nilai etnosains. Mitra kegiatan ini adalah SDN 101749 Klumpang sebagai sekolah dasar mitra pengembangan inovasi pembelajaran. Metode pelaksanaan meliputi lima tahap utama, yaitu sosialisasi, pelatihan, penerapan teknologi, pendampingan, dan evaluasi. Hasil kegiatan menunjukkan peningkatan signifikan pada literasi sains siswa, dengan nilai rata-rata pretest–posttest sebagai berikut: pemahaman konsep sains meningkat dari 56 menjadi 88 (+32), analisis etnosains dari 56 menjadi 84 (+28), dan keterampilan observasi dari 56 menjadi 86 (+30), sehingga rata-rata keseluruhan meningkat sebesar 30%. Selain itu, terjadi peningkatan kompetensi guru dalam mengintegrasikan AR dan kearifan lokal ke dalam pembelajaran. Dengan dukungan pelatihan dan pendampingan berkelanjutan, program ini membuktikan bahwa kolaborasi antara teknologi dan budaya lokal mampu menciptakan pembelajaran sains yang interaktif, kontekstual, dan relevan dengan tantangan pendidikan abad ke-21. Kata Kunci: Literasi Sains, Augmented Reality, Etnosains, Sekolah Dasar